2022
DOI: 10.21037/jtd-21-1199
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated right ventricular assist device with a percutaneous dual-lumen cannula as a bridge to lung transplantation

Abstract: Background: Oxygenated right ventricular assist device (oxyRVAD) placement has become more streamlined with the introduction of the dual-lumen pulmonary artery cannula. Peripherally cannulated oxyRVAD may provide oxygenation support with right heart support as an alternative to venoarterial extracorporeal membrane oxygenation (ECMO) as a bridge to lung transplantation.Methods: A single-institution, retrospective analysis was performed on patients placed on oxyRVAD with a dual-lumen pulmonary artery cannula wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In conclusion, the patients that were treated with a right ventricular assist device (RVAD) using the Protek Duo cannula had comparably better survival rates and fewer complications than other tpRVAD systems [ 48 ]. This supports the fact that the Protek Duo cannula is a safe and feasible treatment for patients who may develop acute right heart failure after left ventricular assist device (LVAD) implantation [ 46 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 64%
See 1 more Smart Citation
“…In conclusion, the patients that were treated with a right ventricular assist device (RVAD) using the Protek Duo cannula had comparably better survival rates and fewer complications than other tpRVAD systems [ 48 ]. This supports the fact that the Protek Duo cannula is a safe and feasible treatment for patients who may develop acute right heart failure after left ventricular assist device (LVAD) implantation [ 46 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 64%
“…This improves oxygenation and relieves both the right atrium and ventricle of the heart. Thus, it also helps prevent complications related to arterial cannulation in patients waiting for lung transplantation with end-stage lung disease, preventing peripheral arterial cannulation or central cannulation [ 42 , 46 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
“…Sinha et al also reported two cases in which a ProtekDuo was used as a bridge to heart-lung and LT ( 51 ). Harano et al reported outcomes of four patients with idiopathic pulmonary fibrosis who were placed on ProtekDuo in V-P configuration as a bridge to transplantation, all of whom underwent double LT ( 52 ). There was one in-hospital mortality due to superimposed pseudomonas pneumonia with influenza virus infection on postoperative day 97, while the other three were alive at 2-year follow up.…”
Section: Newer and Atypical Uses Of Protekduomentioning
confidence: 99%
“…There is also a data suggesting an association between denovo HLA-sensitization and ECMO bridging [40 & ]. Newer variations on ECLS have begun to gain traction, including the oxygenated right ventricular assist device (oxy-RVAD) to provide both oxygenation and right heart support [41][42][43]. It has been our practice for actively listed patients requiring endotracheal intubation who are deemed inappropriate for ECLS to undergo an early tracheostomy, allowing for active participation in physical therapy [44].…”
Section: Bridgingmentioning
confidence: 99%